2000
DOI: 10.1302/0301-620x.82b8.10330
|View full text |Cite
|
Sign up to set email alerts
|

Rigid internal fixation of fractures of the proximal humerus in older patients

Abstract: In 42 elderly patients, 33 women and nine men with a mean age of 72 years, we treated displaced fractures of the proximal humerus (34 three-part, 8 four-part) using a blade plate and a standard deltopectoral approach. Functional treatment was started immediately after surgery. We reviewed 41 patients at one year and 38 at final follow-up at 3.4 years (2.4 to 4.5). At the final review, all the fractures had healed. The clinical results were graded as excellent in 13 patients, good in 17, fair in seven, and poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
20

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 28 publications
4
86
0
20
Order By: Relevance
“…In fact, this scale is not only founded on the mobility but also on the strength and is finalized to the evaluation of young patients, able to lift 12 kg, while our patients were 68 years old on average. The mean Constant-Murley score was 70 points, comparable to that (73 points) of a recent study of elderly people [16].…”
Section: Displaced Fractures At Low Risk Of Osteonecrosis Insupporting
confidence: 81%
See 1 more Smart Citation
“…In fact, this scale is not only founded on the mobility but also on the strength and is finalized to the evaluation of young patients, able to lift 12 kg, while our patients were 68 years old on average. The mean Constant-Murley score was 70 points, comparable to that (73 points) of a recent study of elderly people [16].…”
Section: Displaced Fractures At Low Risk Of Osteonecrosis Insupporting
confidence: 81%
“…16 This metaphyseal type III fracture (a) was accompanied by a diaphyseal fracture, which required a cerclage (b). This case is also interesting because of the lowering of the humerus in the postoperative period (c), which nevertheless was readily recovered after removing the wires (d, e) a b c d e…”
Section: Referencesmentioning
confidence: 99%
“…Canbora et al [15] in their study has a total of 29 patients of which 9 were 2-part fracture, 15 were 3-part fractures and 5 were 4-part fractures. Hintermann et al [17] in their series had a total of 42 patients with proximal humerus fractures of which 34 were 3-part fractures and 8 were 4-part fractures. In our study we observed that 2-part proximal humerus fractures occurred in a greater frequency in the elderly compared to the other types.…”
Section: Discussionmentioning
confidence: 99%
“…Hintermann et al (12) descreveram bons resultados em fraturas fixadas com placa-lâmina. Porém, recentemente, Meier et al (13) relataram 33% de complicações com esse método; em 22% dos pacientes houve protrusão da placa-lâmina na articulação do ombro.…”
Section: Discussionunclassified